STOCHASTIC PROCESSES AND SOME APPLICATIONS - Mioara VARGA; Mihaela GHIDURUS; Alex CALIN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In this paper, we discuss about some applications to the birth and death process in biology and in the theory of waiting. First, we introduce some theoretical notions about the stochastic processes and we define the Markov chain and the Poisson process. Afterwards, we consider two processes of birth: "The Poissonian tide of particles” and “ The Yule-Furry process”, that have multiple applications, the theory of waiting being one of them. Finally, by using the theoretical concept presented above, we solve two examples: the first is a problem from veterinary medicine, and the second one is an example of the model M/M/1 from agriculture, which means if the entrance, the time of serving and the number of stations are given, we'll calculate the number of the biological units in system, the medium number of the applicants in line and the medium time of waiting.